EVALUASI PELAKSANAAN KEGIATAN UPKD ANDALAS UNTUK SEKTOR PERTANIAN DARI DANA BENGKULU REGIONAL DEVELOPMENT PROJECT (BRDP) DI DESA TAPAK GEDUNG KABUPATEN KEPAHIANG - Nufus, Nurhayatin; Nabiu, Musriyadi; Susilawati, Tati (Jurnal AGRISEP, 2005)
This research was aimed at exploring the implementation of economic scheme program at UPKD Andalas and analyzing income discrepancy between member and non-member of UPKD Andalas.  This research was conducted at UPKD Andalas District Kepahiang. Data was collected to 27 members and 21 non-members.  These respondents were classified into paddy and coffee farmers. The results show that the implementation of economic scheme program was not running optimal yet which is indicated by unimplemented the rights and dutiesl.  Rank spearman test show tyha relationship between the implementation level of the program and farmer income.  However, there is insignificant income discrepancy between member and non-member incomes.